Regarding a case with marked elevation of ST-segment during an electric treadmill testing - Roberto Gonzalez Guerra; Jhonathan Franklin Quispe Santos; Eduardo Rivas Estany; Sherien Sixto Fernández; Juan Antonio Álvarez-Gómez (ECIMED, 2011)
Our patient was a 55 year-old-man, black race, a heavy smoker and he suffer fromhypertension. He had presented angina on effort and repose for several weeks. He wasremitted to Cardiovascular Institute for going to realize an electric treadmill testing, forarterial coronary disease probably. During the effort test the patient had presented apronounced elevation of ST-segment, to charge low, in precordials derivations and lowerin the inferior side, accompanied of angina. This event diminished with sublingual nitroglycerin.He was interned for to realize an angiographic study, and was detected onlyone lesion of a 20% in medial left coronary artery and a little right coronary artery. The patients was discharge with diagnose of vasospastic angina, a treatment regimen of aspirin,beta- blockers and calcium antagonists was established, improvement the symptomof angina.